2015
DOI: 10.1164/rccm.201412-2148oc
|View full text |Cite
|
Sign up to set email alerts
|

A Sex-Specific MicroRNA-96/5-Hydroxytryptamine 1B Axis Influences Development of Pulmonary Hypertension

Abstract: Rationale: Females are predisposed to pulmonary arterial hypertension (PAH); evidence suggests that serotonin, mutations in the bone morphogenetic protein receptor (BMPR) II gene, and estrogens influence development of PAH. The 5-hydroxytryptamine 1B receptor (5-HT 1B R) mediates human pulmonary artery smooth muscle cell (hPASMC) proliferation.Objectives: We aimed to determine whether selected microRNAs (miRNAs) expressed in PASMCs are influenced by sex, BMPR-II mutations, and estrogens, and contribute to PASM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 55 publications
0
62
1
1
Order By: Relevance
“…One potential theory to reconcile these discrepancies would be that the same prosurvival and anti-apoptotic properties of E 2 that are beneficial in the pressure-overloaded RV may contribute to increased pulmonary vascular wall cell proliferation and remodeling. While we did not note worsening PA remodeling with E 2 in our laboratory's prior studies of SuHx or chronically hypoxic rats (rather, we noted improvement) (11,32), E 2 may worsen PA remodeling in the context of genetic alterations in BMPR2 or serotonin signaling (2,43,44,63,64). E 2 may be "good for the RV" but, at least in certain contexts, "bad for the pulmonary vasculature" (31,34).…”
Section: Discussioncontrasting
confidence: 50%
“…One potential theory to reconcile these discrepancies would be that the same prosurvival and anti-apoptotic properties of E 2 that are beneficial in the pressure-overloaded RV may contribute to increased pulmonary vascular wall cell proliferation and remodeling. While we did not note worsening PA remodeling with E 2 in our laboratory's prior studies of SuHx or chronically hypoxic rats (rather, we noted improvement) (11,32), E 2 may worsen PA remodeling in the context of genetic alterations in BMPR2 or serotonin signaling (2,43,44,63,64). E 2 may be "good for the RV" but, at least in certain contexts, "bad for the pulmonary vasculature" (31,34).…”
Section: Discussioncontrasting
confidence: 50%
“…PAH. A sex-specific decrease in miR-96 was found to increase expression of the 5-hydroxytryptamine 1B receptor (42), thus predisposing to alteration of serotonin signaling and proliferative signals in the diseased pulmonary vasculature. Separately, a sex-specific interaction of miR-29 was described with estrogen metabolism (43), suggesting a molecular mechanism correlating female hormone signaling with the predisposition of PAH in women in the general population.…”
Section: Vasoconstrictionmentioning
confidence: 98%
“…For example, oestrogen appears to exert protective (e.g. vasodilator and anti-proliferative) effects in hypoxia-induced PH and MCT-PH [14,15], while it promotes pulmonary artery remodelling in the setting of BMPR2 mutations or increases in serotonin signalling [11,26]. Our laboratory demonstrated that oestrogen exerts anti-proliferative effects in the setting of hypoxia, but not during normoxia [14].…”
Section: Sex Steroids Exhibit Context-dependent Effects On Pulmonarymentioning
confidence: 64%